INTEGRASI MANAJEMEN SUMBER DAYA MANUSIA DAN KODE ETIK INSINYUR DALAM MENDORONG PEMBANGUNAN BERKELANJUTAN (SUATU KAJIAN LITERATUR) - Maudhy Satyadharma (Universitas Islam Balitar, 2025)
Sustainable development demands a multidimensional approach that emphasizes not only technical and economic aspects, but also ethical dimensions and human resource (HR) management. In the context of the engineering profession, the success of sustainable development is largely determined by the quality of engineers as the main actors in the planning, design, and implementation of development projects. This article aims to examine the integration of HR management and the engineering code of ethics in promoting sustainable development through a literature review approach. The method used is a literature study of various scientific sources in the form of books, national and international journals, and policy documents related to HR management, engineering professional ethics, and sustainable development. The results of the study indicate that sustainable development requires a strong integration between technical competence and moral integrity of professional actors, especially engineers. This study shows that human resource management and the engineering code of ethics are two strategic instruments that complement each other in promoting sustainable development. The integration of the two has been proven to be able to create synergy between technical performance achievements and ethical responsibilities, so that development can take place consistently, accountably, and long-term.